Simon Stock and the Scapular Vision - Copsey, Richard (The journal of ecclesiastical history, 1999)
St Simon Stock is an elusive thirteenth-century Carmelite saint of whom it may be said that very little is known but about whom much has been written. The details of his life and even the fact of his existence have aroused considerable controversy over the centuries. In part the lack of firm information could be attributed to the fact that, until recently, the early history of the Carmelites, or Whitefriars, was little known and clouded by legendary claims about the order being founded on Mount Carmel by the prophet Elijah. In addition, church historians have tended to focus on the larger and better documented Franciscan and Dominican orders. The Carmelites, although numerically fewer, were nevertheless a significant presence in medieval England comprising at their peak some thirty-nine communities and a total approaching 1,000 friars. Fortunately, in the past few years, the quantity of published research on Carmelite history has increased significantly.